An Ordinance to Prevent the Carrying of Loaded or Concealed Weapons Within the Limits of the City of Hoboken, in Hoboken, N.J., Ordinances 240-41 (1892) - (:unkn) unknown (My University, 1885)
That it shall not be lawful for any person or persons (excepting policemen and private watchmen when on duty), within the corporate limits of the city of Hoboken, to carry, have or keep concealed on his or her person any instrument or weapon commonly known as slung shot, stilletto, billy, sandclub or metal knuckles, and any dirk or dagger (not contained as a blade of a pocket knife), and loaded pistol or other dangerous weapon
Keywords: CARRY - CONCEALED